Chemically enhanced primary treatment of sewage using the recovered alum from water treatment sludge in a model of hydraulic clari-flocculator. (October 2017) - Ayoub, Mohamed; Afify, Hafez; Abdelfattah, Abdallah
Abstract: The present study provides a cost-effective and eco-friendly approach for chemically enhanced primary treatment (CEPT) of wastewater. This approach based on two aspects in the same time. The first aspect is utilization of the recovered alum from water treatment sludge as a coagulant and then comparing the obtained results with those obtained from using the fresh alum. Furthermore, the second aspect involved an investigation of the hydraulic clari-flocculator model to complete the process of CEPT of wastewater in a simple and low-cost model. The obtained results using the recovered alum revealed that the removal efficiencies of BOD5, COD, TSS, PO4, and NO3 reached up to 85.5%, 74.5%, 84.46%, 95.8% and 30.4% respectively. In general, the maximum differences in the removal efficiencies results from utilization of the fresh and the recovered alum were just 2.94% of BOD5, 8.11% of COD, 1.68% of TSS, 3.11% of PO4, and 11.33% of NO3 . Therefore, the slight differences in the removal efficiencies of various wastewater characteristics were obtained when comparing the fresh alum with the recovered alum. However, the recovered alum is significantly better than the fresh alum according to viewpoint of the environmental impact.